Efficiency in natural product total synthesis - Huang, Peiqiang, 1962-; Yao, Zhu-Jun; Hsung, Richard P. (Wiley, 2018)
Uniting the key organic topics of total synthesis and efficient synthetic methodologies, this book clearly overviews synthetic strategies and tactics applied in total synthesis, demonstrating how the total synthesis of natural products enables scientific and drug discovery. This book : Focuses on efficiency, a fundamental and important issue in natural products synthesis that makes natural product synthesis a powerful tool in biological and pharmaceutical science and describes new methods like organocatalysis, multicomponent and cascade reactions, and biomimetic synthesis.